Stability and Hopf Bifurcation for a Delayed Computer Virus Model with Antidote in Vulnerable System - Zizhen Zhang; Yougang Wang; Massimiliano Ferrara (Journal of Control Science and Engineering)
A delayed computer virus model with antidote in vulnerable system is investigated. Local stability of the endemic equilibrium and existence of Hopf bifurcation are discussed by analyzing the associated characteristic equation. Further, direction of the Hopf bifurcation and stability of the bifurcating periodic solutions are investigated by using the normal form theory and the center manifold theorem. Finally, numerical simulations are presented to show consistency with the obtained results.